SAT0114 IMPACT OF DOSE TAPERING REIMBURSEMENT POLICY ON PRESCRIPTION PATTERN OF ADVANCED THERAPY FOR RHEUMATOID ARTHRITIS IN TAIWAN. (2nd June 2020) - Tang, C. H.; Chang, C. L.; Shau, W. Y.; Hsin, C. Y.; LI, K. J.
Abstract : Background: Rheumatoid arthritis (RA) patients treated with advanced therapy (biologic disease-modifying antirheumatic drugs and targeted synthetic disease-modifying antirheumatic drugs) may be considered dose tapering after reaching treatment goal. 1 In EULAR 2016 recommendations, dose reduction can be considered if patients reach sustained remission. 2 A dose tapering policy of advanced therapy was introduced in the treatment guideline of RA since 2014 under the National Health Insurance (NHI) in Taiwan. The new reimbursement policy requests the dosage to be tapered in patients who received advanced therapy for 2 years and reached low disease activity defined by DAS28 (ESR). Objectives: This retrospective study aims to investigate the impact of dose tapering policy on prescription pattern of advanced therapy for RA patients in Taiwan. Methods: This study was an observational retrospective analysis on the population-based National Health Insurance Research Database (NHIRD) in Taiwan. Patients with RA aged ≥18, initiated an index advanced therapy - abatacept, adalimumab, etanercept, golimumab, tocilizumab, or tofacitinib, during 2011-2017 were included (Figure 1 ). Patients were followed-up until the index advanced therapy was switched/discontinued or the end of data, whichever came first. The 4-week moving average of proportion of days covered (PDC) of the index therapy within each 12-week period were assessed. The outcome variable was whether dose tapering occurred which was defined as PDC being less than 0.5. The odds ratios (ORs) and the 95% confidence intervals (CIs) were estimated using Generalized Estimating Equation (GEE) with logistic specification to examine the independent effect of tapering policy and treatment duration on the probability of dose tapering, after controlling for age, sex, and index advanced therapy. Results: The study comprised 9, 094 patients initiated advance treatment for RA, with mean age of 57.3 (SD 13.3) years and 78.8% were female. The median PDC dropped remarkably after 28 months since treatment initiation (Figure 2 ). Probability of dose tapering increased significantly when treatment duration ≥24-month (OR=2.73, p <0.001). When treatment duration < 24-month, Dose Tapering policy was not significantly associated with tapering prescription. However, implementation of the policy further increased the probability of dose tapering for patients with treatment duration ≥ 24-month, OR for interaction of policy by duration was 1.17, and test for interaction p =0.014. There were about 3 times increase in the odds of dose tapering probability for patient treated longer than 24 months after the policy implemented in April 2014. Conclusion: For RA patients, PDC of advanced therapy dropped notably after patients received advanced therapy for more than 24 months. The tapering policy implementation significantly increased the probability of dose tapering of advanced therapy in patients with treatment duration ≥ 24 months. References: [1]Lenert A, Lenert P. Clin Rheumatol. 2017;36(1):1-8. [2]Smolen JS, et al. Ann Rheum Dis. 2017;76(6):960-977. Acknowledgments: Research is sponsored by Pfizer Ltd. Disclosure of Interests: Chao-Hsiun Tang: None declared, Chia-Li Chang: None declared, Wen-Yi Shau Employee of: Pfizer, Chih-Yi Hsin Employee of: Pfizer, Ko-Jen Li Speakers bureau: Speaker fee from Pfizer, Abbvie, Roche, Bristol-Myers Squibb, Eli Lilly and Johnson & Johnson